The effects of robot-assisted laparoscopic surgery with Trendelenburg position on short-term postoperative respiratory diaphragmatic function - Xue, Shuo; Wang, Dan; Tu, Hong-Qin; Gu, Xiao-Ping; Ma, Zheng-Liang; Liu, Yue; Zhang, Wei (BMC anesthesiology, 2024)
Objective To study how Pneumoperitoneum under Trendelenburg position for robot-assisted laparoscopic surgery impact the perioperative respiratory parameters, diagrammatic function, etc. Methods Patients undergoing robot-assisted laparoscopic surgery in the Trendelenburg position and patients undergoing general surgery in the supine position were selected. The subjects were divided into two groups according to the type of surgery: robot-assisted surgery group and general surgery group. ① Respiratory parameters such as lung compliance, oxygenation index, and airway pressure were recorded at 5 min after intubation, 1 and 2 h after pneumoperitoneum. ② Diaphragm excursion (DE) and diaphragm thickening fraction (DTF) were recorded before entering the operating room (T 1 ), immediately after extubation (T 2 ), 10 min after extubation (T 3 ), and upon leaving the postanesthesia care unit (T 4 ). ③ Peripheral venous blood (5 ml) was collected before surgery and 30 min after extubation and was analyzed by enzyme-linked immunosorbent assay to determine the serum concentration of Clara cell secretory protein 16 (CC16) and surfactant protein D (SP-D). Result ① Compared with the general surgery group ( N = 42), the robot-assisted surgery group ( N = 46) presented a significantly higher airway pressure and lower lung compliance during the surgery( P < 0.001). ② In the robot-assisted surgery group, the DE significantly decreased after surgery ( P < 0.001), which persisted until patients were discharged from the PACU ( P < 0.001), whereas the DTF only showed a transient decrease postoperatively ( P < 0.001) and returned to its preoperative levels at discharge ( P = 0.115). In the general surgery group, the DE showed a transient decrease after surgery( P = 0.011) which recovered to the preoperative levels at discharge ( P = 1). No significant difference in the DTF was observed among T 1 , T 2 , T 3 , and T 4 . ③ Both the general and robot-assisted surgery reduced the postoperative serum levels of SP-D ( P < 0.05), while the robot-assisted surgery increased the postoperative levels of CC16 ( P < 0.001). Conclusion Robot-assisted laparoscopic surgery significantly impairs postoperative diaphragm function, which does not recover to preoperative levels at PACU discharge. Elevated levels of serum CC16 after surgery suggest potential lung injury. The adverse effects may be attributed to the prolonged Trendelenburg position and pneumoperitoneum during laparoscopic surgery.